2021
DOI: 10.1126/sciadv.abg4617
|View full text |Cite
|
Sign up to set email alerts
|

An asymmetric mechanical code ciphers curvature-dependent proprioceptor activity

Abstract: A repetitive gait cycle is an archetypical component within the behavioral repertoire of many animals including humans. It originates from mechanical feedback within proprioceptors to adjust the motor program during locomotion and thus leads to a periodic orbit in a low-dimensional space. Here, we investigate the mechanics, molecules, and neurons responsible for proprioception in Caenorhabditis elegans to gain insight into how mechanosensation shapes the orbital trajectory to a well-defined limit cycle. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 99 publications
(162 reference statements)
1
26
0
Order By: Relevance
“…The isolation of primary C. elegans neurons was performed following a previously described method. 106 Briefly, after synchronization, worms were seeded onto peptone-enriched plates and incubated at room temperature (RT). Once populated with eggs, the plates were washed with Milli-Q H 2 O and the eggs collected.…”
Section: Methodsmentioning
confidence: 99%
“…The isolation of primary C. elegans neurons was performed following a previously described method. 106 Briefly, after synchronization, worms were seeded onto peptone-enriched plates and incubated at room temperature (RT). Once populated with eggs, the plates were washed with Milli-Q H 2 O and the eggs collected.…”
Section: Methodsmentioning
confidence: 99%
“…On the last day of developmental assessment, the adult animals were placed on the new plate and the moving trace on bacterial lawn captured. The locomotion behavior was observed under the lab-built microscope (WormTracker (Das et al . 2021)).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, extrachromosomal arrays contain large copy numbers of the injected DNA, which often causes overexpression artefacts, but have the advantage that transgenes become visible even beyond their native levels. For example, many fluorescent tags to endogenous proteins are poorly visible due to their low expression levels and promoter activity (Das et al 2021; Walker et al 2000). The problem of unstable inheritance can be mitigated by integrating the transgenic array.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, Feng et al further demonstrated that, in the absence of force, the initial TCR calcium triggering requires much higher pMHC ligand density-690 folds higher than physiologically observed [38]. Moreover, Das et al performed OT-DFS to pull membrane tethers from Caenorhabditis elegans DAV neurons with the positive and the negative tension gradient [37]. They observed that the subsequential calcium mobilization upon increased membrane tension was associated with the activation of the TRP-4 channel and nompC (no mechanoreceptor potential C), which consequentially confines the neuronal activity for movement.…”
Section: Motor Stepping In Vitromentioning
confidence: 99%